Relationship between Helicobacter Pylori infection and metabolic syndrome components in adults - Jiang, Yan-fei; Zhong, Long; Guo, Jing-jing; Wang, Qiao-fen; Gu, Jia-xu; Huang, Jia-yu; Liu, Yan-jing; Lin, Yuan; Lu, Dong-hui; Lian, Xiao-fen (Frontiers in Endocrinology, 2025)
Background and aimHelicobacter pylori (H. pylori, HP) infection plays a significant role in the development and progression of various intra-gastric and extra-gastric diseases. Its infection is associated with numerous factors, including a series of metabolic-related diseases, and the potential connections between them remain highly controversial. Meanwhile, the prevalence of metabolic diseases has been increasing exponentially with changes in economic levels and lifestyles. Exploring the correlations and potential mechanisms between HP and metabolic diseases is crucial for future disease prevention and control. Due to the ongoing controversy surrounding its relevance and the absence of articles investigating the metabolic-related mediating mechanisms and threshold effects of related metabolic diseases leading to HP infection, this study holds significant importance for guiding future lifestyle and disease control.MethodsBy collecting relevant test and examination indicators from 7,387 participants at Peking University Shenzhen Hospital, we analyzed the potential pathogenic mechanisms using statistical methods such as regression analysis, mediation analysis, and threshold analysis.ResultsWe found that factors such as blood glucose levels (fasting blood glucose (FBG), glycosylated hemoglobin (HbA1c)), Body Mass Index (BMI), and blood pressure (Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP)) were the main risk factors influencing the target outcomes in this study, while higher levels of Albumin (Alb) may have a certain protective effect, with BMI playing a particularly significant role among these factors.ConclusionThis discovery has deepened our understanding of metabolic diseases, BMI, related metabolic indicators, and HP infection.